(untitled) (REMUNOM, 2024)
Inclusive Education can be envisioned as a contemporary educational concept aimed at ensuring the right to education for everyone. It entails equality of opportunities and the valuing of human differences, encompassing ethnic, social, cultural, intellectual, physical, sensory, and gender diversities. In this context, the main objective of this article is to address the evolution and importance of inclusive education in Brazil. The methodology adopted for this article was both quantitative and qualitative, relying on bibliographic research. Data from school enrollment records for the years 2010, 2015, and 2020, published by the National Institute for Educational Studies and Research Anísio Teixeira and the Department of Educational Statistics, were also used. In this regard, the data suggest a notable increase in the number of enrollments of students with disabilities in regular education in recent years. This growth indicates positive progress towards inclusion, reflecting a greater recognition of the importance of integrating these students into common educational environments. However, it is crucial that this increase is accompanied by ongoing improvements in the conditions and resources provided to ensure that these students not only enter regular schools but also remain and succeed in their educational journey.